NF-κB and JNK mediated apoptosis and G0/G1 arrest of HeLa cells induced by rubiarbonol G, an arborinane-type triterpenoid from Rubia yunnanensis. (28th June 2018) - Zeng, Guang-Zhi; Wang, Zhe; Zhao, Li-Mei; Fan, Jun-Ting; Tan, Ning-Hua
Abstract: Ethnopharmacological relevance: Rubia yunnanensis is a medicinal plant mainly grown in Yunnan province in Southwest China, and its root named "Xiaohongshen" has been used as a herb in Yunnan for the treatment of cancers. Three major types of chemical components, Rubiaceae-type cyclopeptides, quinones, and triterpenoids, were identified from R. yunnanensis, in which some of compounds including rubiarbonol G (RG), a unique arboriane-type triterpenoid, showed cytotoxicity on cancer cells. But the cytotoxic mechanism of RG has not been reported. Aim of the study: To investigate the cytotoxic mechanism of RG on cancer cells. Materials and methods: RG was evaluated its cytotoxicity on 7 cancer cell lines by the SRB assay, and detected the effect on apoptosis and cell cycle arrest by Annexin V-FITC/PI apoptosis assay and DNA contents analysis. The expression and activity of apoptosis and cell cycle related proteins were also investigated by western blot and caspase activity assay. Furthermore, the effect of RG on NF-κB signaling was also tested by luciferase assay, western blot, and immunofluorescence staining. Results: RG showed potent cytotoxicity on 7 human cancer cell lines, whose activity was attributed to apoptosis induction and G0 /G1 arrest in HeLa cells. Results from the mechanism study showed that RG promoted the activation of ERK1/2 and JNK pathway in MAPK family, which in turn increased the expression of p53, thereby triggering the G0 /G1 arrest through p53/p21/cyclin D1 signaling. Moreover, RG-mediated JNK activation down-regulated the expression of the anti-apoptotic protein Bcl-2, which caused the release of cytochrome c to the cytosol and activated the cleavage of caspase cascade and poly(ADP-ribose) polymerase, thereby inducing apoptosis in HeLa cells. In addition, RG was also found to inhibit the activation of NF-κB signaling by down-regulating the expression and attenuating the translocation to nucleus of NF-κB p65, by which the down-stream p53, cyclin D1, Bcl-2, and caspases were regulated, thereby triggering apoptosis and G0 /G1 arrest in HeLa cells. Conclusion: These results indicated that RG induces mitochondria-mediated apoptosis and G0 /G1 cell cycle arrest by activation of JNK signaling as well as inactivation of NF-κB pathway in HeLa cells, which suggests that RG is one of the key active ingredients accounting for the anti-tumor effect of R. yunnanensis . Graphical abstract: